PENGEMBANGAN USAHA TEPUNG IKAN DI DESA NELAYAN PUGER WETAN - Halimatus Sa’diyah; Alfian Futuhul Hadi; Nasrul Ilminnafik (UII, 2016)
Puger Wetan is the largest fisheries center in Jember. One of the fish type produced is SardinellaLemuru. Due to its small size and prickly nature, it is rarely consumed directly. It is commonly sold as raw material for canned sardines. Canned sardines manufacture needs fresh Lemuru, because it will cause itching on the tongue if not fresh. Whereas, fishermen mostly piled the fish in the boat hatch then gave ice cubes, so that the majority of it will no longer be fresh when arrived in the mainland because its perishable nature due to its thin skin.As the result, most of fishermen’s catch is not feasible for canned sardines and become leftovers. During this time, it will be sold at a low price. Fish leftovers that are not absorbed by the market aredumped into the river, becomingleftovers. The waste pollutes the environment and harms the health and hygiene. There will be more wastes during the fishing season, as more and more lemuru leftovers are dumped. This activity aims to resolve the problem by transforming the leftovers into fish meal, using appropriate tech machines. The activities are carried out in several stages. The first stage is the counseling about the negative impact of fisheries waste and the possibility of utilizing it into fish meal, also about the business opportunity that is still potential because domestic demand is still not yet met. The explanation of the importance of business management was also given.The third stage is the practice of making fish meal with the help of tools that have been previously converted technology. The fourth stage is the evaluation of activities for the benefit of partnering groups. Lemuru leftover utilization into fish meal is one of the important components in animal feed which can increase the fishermen income, while reducing environmental pollution.